2012
DOI: 10.1021/ml300106p
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Analogues with Antibacterial Activity Are Potent Inhibitors of Biotin Protein Ligase

Abstract: There is a desperate need to develop new antibiotic agents to combat the rise of drug-resistant bacteria, such as clinically important Staphylococcus aureus. The essential multifunctional enzyme, biotin protein ligase (BPL), is one potential drug target for new antibiotics. We report the synthesis and characterization of a series of biotin analogues with activity against BPLs from S. aureus, Escherichia coli, and Homo sapiens. Two potent inhibitors with K i < 100 nM were identified with antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…Further, the mainchain of the ABL loop is in the same position even in the absence of the adenosyl moiety (the sidechains of this loop were not defined in the electron density). These structures, together with a recently reported structure of Sa BPL with biotin‐based ligands bound in the active site, show that any biotin ligand is sufficient to stabilize the BBL and to result in the formation of an Sa BPL dimer.…”
Section: Resultssupporting
confidence: 57%
“…Further, the mainchain of the ABL loop is in the same position even in the absence of the adenosyl moiety (the sidechains of this loop were not defined in the electron density). These structures, together with a recently reported structure of Sa BPL with biotin‐based ligands bound in the active site, show that any biotin ligand is sufficient to stabilize the BBL and to result in the formation of an Sa BPL dimer.…”
Section: Resultssupporting
confidence: 57%
“…In a study seeking to validate biotin biosynthesis as a potential target for the development of new antibiotics, the authors have demonstrated that de novo biotin synthesis is essential for M. tuberculosis to establish and maintain a chronic infection [144]. In another study, analogs of biotin have been synthesized and have demonstrated antimicrobial activity through the inhibition of biotin protein ligase (BPL) [145]. Taken together, there appears to be a great potential for targeting biotin biosynthesis, not only in antibacterial drug development but perhaps fungal BPL could serve as a potential drug development target for new antifungal agents.…”
Section: Miscellaneous Antifungal Agentsmentioning
confidence: 99%
“…20 The antibacterial activity of the compounds was also determined using S. aureus strain ATCC 49775. 18 Growth of the bacteria 20 h post-treatment was measured spectrophotometrically at 600 …”
Section: B Iotin Protein Ligase (Bpl) Catalyzes the Reaction Of Biotinmentioning
confidence: 99%